Hepatitis C therapy with HCV NS5B polymerase inhibitors. (June 2013) - Soriano, Vincent; Vispo, Eugenia; de Mendoza, Carmen; Labarga, Pablo; Fernandez-Montero, Jose Vicente; Poveda, Eva; Treviño, Ana; Barreiro, Pablo
<x xml:space="preserve">Abstract</x> Introduction: Several HCV polymerase inhibitors are in advanced stages of clinical development. They are nucleos(t)ide and non-nucleoside analogs. Nucleos(t)ides inhibit viral replication acting as chain terminators whereas non-nucleosides block allosterically the HCV polymerase. Sofosbuvir is an uridine analog and currently the most promising HCV polymerase inhibitor, being active across all HCV genotypes. It has good tolerability and a robust barrier to resistance. In contrast, non-nucleoside analogs have low to moderate antiviral potency, a low barrier to resistance and inhibit only HCV genotype 1. Areas covered: Studies conducted with distinct HCV polymerase inhibitors as part of interferon-free combinations have opened a new landscape in which shorter treatment duration and all-oral regimens are envisioned as the future curative treatment for most chronic hepatitis C patients. Expert opinion: Antiviral drug development for HCV is progressing at a feverish pace. Amongst HCV polymerase inhibitors, sofosbuvir has positioned as unique companion with ribavirin as therapy for most HCV genotypes 2 or 3, and along with NS5A inhibitors for other HCV genotypes. Non-nucleoside HCV polymerase inhibitors are being developed only as part of all-oral combinations with protease inhibitors. The expected high cost of DAAs will preclude their prompt and wider use, allowing room for using alternative cheaper options in easier-to-treat patient populations.